Citation uses and perceptions in the literature review of PhD theses by EFL Arab postgraduates - Jomaa, Nyef Jomaa (2017)
Citation in academic writing is significant but challenging for novice writers. In spite of the increasing studies on the use of citations, limited knowledge is available about the use of citations by EFL Arab postgraduates. Hence, this study aimed at determining the use of citations and exploring the perceptions of EFL Arab postgraduates and PhD supervisors on the use of citations. This qualitative study examined 20 literature reviews from PhD theses in Information Technology and Applied Linguistics produced by EFL Arab postgraduates. The use of citations was analysed using Halliday‘s Systemic Functional Linguistics. The linguistic features obtained from the lexico-grammatical analysis were employed in the evaluation of the use of citations. Nine EFL Arab postgraduates and five PhD supervisors from Applied Linguistics and Information Technology were interviewed to highlight the challenges encountered in using citations. The findings revealed that full declarative clauses were used in the citations. Material, relational, verbal, mental, existential, and behavioural processes were used to realize the Transitivity System. Clause complexes in citations were joined hypotactically and paratactically to realize Projection, Expansion, and a combination of Projection and Expansion as logicosemantic relations. Textual, Interpersonal, Topical, Predicated, and Marked themes were employed in the clauses of the citations with varied frequencies. The evaluation revealed both appropriate and inappropriate use of clauses in the citations. The interviews with EFL Arab postgraduates revealed the challenges encountered in using citations such as adopting a stance, having insufficient knowledge in using citations, and paraphrasing. The interviews with PhD supervisors also showed that difficulties faced by EFL Arab postgraduates are due to lack of in-depth reading, inability to use citations, poor L2 academic writing skills, and improper positioning of writers‘ stance. The findings of this study, firstly, extended the existing knowledge of linguistic description on the use of citations and, secondly, explored opportunities to develop EAP/ESP courses.